Kebosanan Kerja Sebagai Prediktor Perilaku Cyberloafing Pada Karyawan - Fatiya Halum Husna; Ika Adita Silviandari; Ika Rahma Susilawati (Jurnal Studia Insania, 2020)
Internet using in Indonesia has a rapid increase and encourages the misuse of internet using at a workplace named cyberloafing behavior. Work boredom is one important factor to increase cyberloafing behavior. This study was aimed to determine the job boredom role as a predictor employee’s cyberloafing behavior. This research used a quantitative approach. Questionnaires used to collect data about job boredom and cyberloafing behavior and analyzed by a simple regression method. The subjects are 114 administrative employees using a cluster sampling method. The analysis result showed a significance value (p<0, 05), it means the hypothesis from this research accepted, job boredom has a role as a predictor of cyberloafing behavior on X university’s employee. The data result explained job boredom gives influential contribution as much as 11, 1% towards cyberloafing behavior. The study showed that job boredom as a significant variable for predicting employee’s cyberloafing behavior.